Fabrication of nanosized Al2O3 reinforced aluminum matrix composites by subtype multifrequency ultrasonic vibration. Issue 14 (14th July 2015) - Chen, Xiao-Hui; Yan, Hong
Abstract: Abstract : Nanosized Al2 O3 (Al2 O3np ) reinforced Al7075 composites were fabricated by specially made Al2 O3np containing Mg powder and subtype multifrequency ultrasonic vibration. Compared to traditional techniques, Al2 O3np was effectively dispersed in the matrix by the novel method. Microstructural studies showed that the addition of Al2 O3np caused the grain refinement and that the resultant microstructures of composites depended on the dominant size and degree of Al2 O3np clustering. The grain refinement could be mainly attributed to particle pushing mechanisms. Compared to the matrix alloy, the ultimate tensile and compressive strength of the as-cast composite with 1.5 wt% Al2 O3np fabricated at 800 °C were increased by 59.6% and 42.6%, respectively. Transmission electron microscope analysis showed that high density dislocations and clear interfaces between particles and matrix were present in the grains, suggesting that the superior improvement of mechanical properties can be attributed to dislocation-type strengthening of matrix alloy and load transfer from matrix to hard nanoparticles.